Effectiveness of the Social Assistance Program for The Repair of Uninhabitable Houses (Rutilahu) In the Housing and Settlement Service of Garut Regency - Putri, Amelia Amanda; Rizqullah, Baril Ariq; Anjelia, Putri; Harilan, Fadel Muhammad; Ruyani, Nyi Raden (Dinasti International Journal of Management Science, 2025)
The Uninhabitable House Improvement Social Assistance Program (RUTILAHU) is a government initiative to improve the homes of low-income communities so that they meet health, safety, and comfort standards. This study aims to analyze the effectiveness of the RUTILAHU Social Assistance Program at the Garut District Housing and Settlement Office and identify obstacles in its implementation. The research method uses a descriptive qualitative approach through observation, in-depth interviews, and documentation studies. The effectiveness analysis refers to Budiani's theory with indicators of target accuracy, socialization, goal achievement, and program monitoring. The results show that the program has been on target for low-income communities, but socialization has not been optimal because it depends on village officials. The achievement of objectives was quite good with improvements in housing conditions, although it still depended on community self-reliance. Program monitoring was effective through reports and field monitoring. The main inhibiting factors were the limitations of community self-reliance and dependence on village officials in disseminating information. This study recommends improving socialization strategies and adjusting assistance according to the conditions of the recipients' homes.